2017
DOI: 10.1002/jgm.2959
|View full text |Cite
|
Sign up to set email alerts
|

COX2 and NOS3 gene polymorphisms in women with gestational diabetes

Abstract: The results of the present study suggest that the CC genotype of the COX2 rs6681231 polymorphism is associated with an increased risk of GDM and the need for insulin therapy, whereas the TT genotype of the NOS3 rs1799983 polymorphism may be associated with the need for insulin therapy in women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…In previous studies, the association between polymorphisms and gestational diabetes was studied in three models: additive (number of variant alleles = 0, 1, or 2 for each subject), dominant (variant homozygotes and heterozygotes vs. wildtype homozygotes) and recessive (variant homozygotes vs. heterozygotes and wildtype homozygotes) [10][11][12][13][14][15][16][17]. The best fit was observed for the additive model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, the association between polymorphisms and gestational diabetes was studied in three models: additive (number of variant alleles = 0, 1, or 2 for each subject), dominant (variant homozygotes and heterozygotes vs. wildtype homozygotes) and recessive (variant homozygotes vs. heterozygotes and wildtype homozygotes) [10][11][12][13][14][15][16][17]. The best fit was observed for the additive model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the additive model of genotype-phenotype association was selected for all polymorphisms in this study as it was the simplest and the most appropriate. All polymorphisms that were significantly associated with GDM in univariate analyses in previous studies [10][11][12][13][14][15][16][17] were included as independent variables in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major genetic studies of GDM are candidate gene studies, which have revealed that some single nucleotide polymorphisms (SNPs) in cytokine genes are associated with susceptibility to GDM [12,13]. SNPs within the coding and signal sequences can affect gene transcriptional activity, and then change the production of proteins [14]. Several studies have reported that altered cytokines expression are related to the severity and progression of the GDM [15,16].…”
Section: Introductionmentioning
confidence: 99%